2018
DOI: 10.1016/j.jsg.2017.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Structural heritage, reactivation and distribution of fault and fracture network in a rifting context: Case study of the western shoulder of the Upper Rhine Graben

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 68 publications
8
36
0
Order By: Relevance
“…The most fractured outcrops are located near Andlau, where fracture density exceeds 10 fractures/m. Other authors have observed even higher fracture densities [86], most likely related to this site's location within the Lalaye-Lubine tectonic zone. This zone represents the boundary between the Saxo-Thurigian and Moldanubian domains [87], which extends under the graben and into the Black Forest near Baden-Baden (Figure 1(b)).…”
Section: Fracture Description Of Outcrops Outside the Grabenmentioning
confidence: 62%
See 2 more Smart Citations
“…The most fractured outcrops are located near Andlau, where fracture density exceeds 10 fractures/m. Other authors have observed even higher fracture densities [86], most likely related to this site's location within the Lalaye-Lubine tectonic zone. This zone represents the boundary between the Saxo-Thurigian and Moldanubian domains [87], which extends under the graben and into the Black Forest near Baden-Baden (Figure 1(b)).…”
Section: Fracture Description Of Outcrops Outside the Grabenmentioning
confidence: 62%
“…After chemical separation, 150 ng of Sr was loaded onto a tungsten filament with tantalum activator and analyzed using a Finnigan MAT 262 multicollector solid source mass spectrometer (Bremen, Germany). The 87 Sr/ 86 Sr ratios were normalized to a 86 Sr/ 88 Sr ratio of 0.1194. An average internal precision of 10 ppm (2 sm) was obtained, and the reproducibility of the 87 Sr/ 86 Sr ratio measurements was tested through repeated analyses of the certified NBS987 standard (0.710240).…”
Section: Strontium Isotopes In Dolomite Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The void space in granitic rocks is localized in faults, fractures and adjacent damage zones characterized by elevated microfracture density (Kranz, 1983;Scholz et al, 1993;Vermilye and Scholz, 1999;Zang et al, 2000;Bertrand et al, 2018) or in volumes altered by metamorphic, hydrothermal and weathering processes (Jamtveit et al, 2008(Jamtveit et al, , 2009(Jamtveit et al, , 2011Wyns et al, 2015;Walter et al, 2018). Both fracturing and alteration modify the granite void space geometry and thus affect its physical properties including porosity, permeability, thermal conductivity and retardation capacity (Benson et al, 2006;Brace et al, 1968;Géraud, 1994;Rosener and Géraud, 2007;Schild et al, 2001;Yoshida et al, 2009;Zoback and Byerlee, 1975).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, further mechanical disintegration by fault wear processes produces fine-grained gouge and therefore low threshold size and connectivity impeding permeability (Géraud et al, 1995(Géraud et al, , 2006Bense et al, 2013). Fracturing may be accompanied or succeeded by fracture wall dissolution or precipitation due to chemically active fluids within the fracture network (Boyce et al, 2003;Ferry, 1979;Mazurier et al, 2016;Nishimoto and Yoshida, 2010), which may either increase or decrease the porosity and threshold size (Géraud et al, 2010;Katsube and Kamineni, 1983;Yoshida et al, 2009). Also, volumetric expansion related to alteration of primary sheeted silicates such as biotite may induce local stress variations producing fractures (Lachassagne et al, 2011).…”
Section: Introductionmentioning
confidence: 99%